Analysis of Daily Living Skills Technique of James W Parington and Michael Muller by Teacher of Special Needs School in Deliserdang North Sumatera - Yeanny Suryadi; Hidayat Hidayat; Adi Sutopo; Apiek Gandamana; Albert Pauli Sirait; Abdul Gafur (International Journal of Multidisciplinary Sciences and Arts, 2026)
Developing individuals with independent personal characteristics has become one of the primary goals of education in contemporary Indonesia. Numerous studies have demonstrated that daily activity skill contributes positively to both academic achievement and logical thinking abilities. The objective of fostering daily activity skills is not only directed toward students in general but also toward students with special needs, commonly referred to as Children with Special Needs (CWSN). Through the Ministry of Education, Culture, Research, and Technology, the Indonesian government encourages the development of independent individuals among all students in both mainstream and special education settings. This study aims to examine how teachers in special schools (SLB) develop independent character among students with special needs, particularly students with ASD (Autism Spectrum Autism). The focus on students with ASD is motivated by the continuously increasing prevalence of autism spectrum disorders worldwide, including in Indonesia. This research employed a qualitative approach and was conducted at a special school in Deli Serdang Regency. The findings indicate that teachers adapted and further developed the basic independence skills framework proposed by James W. Partington and Michael Mueller, tailoring its implementation to the individual characteristics and needs of their students. Conclusion: The development of daily living skills for students with autism must consider the unique characteristics of each individual, particularly those in phase A. Basic communication skills can be integrated with other daily living skills activities, and the learning process is more effective when implemented through direct practice and gradual prompting techniques.